2014
DOI: 10.1096/fj.14-258335
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155 potentiates the inflammatory response in hypothermia by suppressing IL‐10 production

Abstract: Therapeutic hypothermia is commonly used to improve neurological outcomes in patients after cardiac arrest. However, therapeutic hypothermia increases sepsis risk and unintentional hypothermia in surgical patients increases infectious complications. Nonetheless, the molecular mechanisms by which hypothermia dysregulates innate immunity are incompletely understood. We found that exposure of human monocytes to cold (32°C) potentiated LPS-induced production of TNF and IL-6, while blunting IL-10 production. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 67 publications
(92 reference statements)
2
41
0
Order By: Relevance
“…A number of these small RNAs have been implicated in mediating inflammation (36,37), and miR-155 levels were shown to be upregulated during inflammatory responses (38, 39). Billeter et al (40) showed that miR-155 played a role in potentiating inflammatory responses. Other studies have shown that miR-155 expression is induced in response to the presence of inflammatory stimuli or activation of Toll-like receptors (TLR) or cytokine stimulation (38,41) and plays a role in regulating germinal center responses (42,43).…”
Section: Hronic Human Immunodeficiency Virus (Hiv) Infection Ismentioning
confidence: 99%
“…A number of these small RNAs have been implicated in mediating inflammation (36,37), and miR-155 levels were shown to be upregulated during inflammatory responses (38, 39). Billeter et al (40) showed that miR-155 played a role in potentiating inflammatory responses. Other studies have shown that miR-155 expression is induced in response to the presence of inflammatory stimuli or activation of Toll-like receptors (TLR) or cytokine stimulation (38,41) and plays a role in regulating germinal center responses (42,43).…”
Section: Hronic Human Immunodeficiency Virus (Hiv) Infection Ismentioning
confidence: 99%
“…Further, proinflammatory effects of microRNA-155 were observed in monocytes. Transfection of monocyte cultures with microRNA-155 mimic led to increased proinflammatory cytokine and chemokine production and expression of the chemokine receptor CCR7, whereas IL-10 secretion and CCR2 expression were decreased [13,14]. These effects of microRNA-155 in monocytes and macrophages were attributed, at least in part, to a decreased repression of the suppressor of cytokine signaling-1 and SH2-containing inositol-5′-phosphatase 1, potent inhibitors of inflammation [5,6,13].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of this miRNA in the proinflammatory response has been thoroughly investigated: among others, miR-155 targets SHIP1 (Fig 2c), a negative regulator of the NF-κB pathway [35,36], and SOCS1 (suppressor of cytokine signalling 1), an effector involved in the homeostasis of Treg cells [37]. This in turn, stimulates the expression of the proinflammatory cytokines TNF-α, IL-6, IL-1β, IL-8 and IL-12, while it reduces the expression of the anti-inflammatory cytokine IL-10 [38,39]. A complex interplay occurs upon infection, as IL-10 itself can reduce miR-155 expression in response to LPS [40].…”
Section: Key Micrornas Involved In Immunitymentioning
confidence: 99%